Contemporary Conversions: Compensatory Needs Or Self-Growth Motives? - Buxant, Coralie (Research in the social scientific study of religion, 2009)
Do people convert to mainstream religions to compensate for deficiency needs or to satisfy self-growth motives? This question is important in the context of secularized societies. In the present study, 180 converts to a variety of mainstream religions completed questionnaires measuring attachment with parents in childhood, adult romantic attachment, needs for closure and cognition, generativity, appreciation of beauty, and existential achievement. Compared to scores from the general population on the same measures, our results suggested the presence of affective and cognitive needs among converts. Except generativity, which was shared by all converts, the presence of other self-growth motives was delimited to specific religions, which could be interpreted in terms of correspondence between supply (people’s motives) and demand (group’s characteristics).